2017
DOI: 10.1515/asn-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Fish Lipids as a Valuable Source of Polyunsaturated Fatty Acids

Abstract: This article presents information about omega-3 (n-3) and omega-6 (n-6) polyunsaturated fatty acid (PUFA) contents in a broad range of commercially important fish species available on Bulgarian fish markets. The aim is to raise consumers' awareness and encourage them to eat fish. Fish species from the Black Sea coast have relatively high proportion of n-3 PUFAs, of which more than 80% is by EPA (eicosapentaenoic acid, C 20:5 n-3) and DHA (docosahexaenoic acid, C 22:6 n-3). Extensive epidemiological studies sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…The high market availability and the increase in market demand of salmon, herring and mackerel, particularly rich in ω3 fatty acids, might be plausibly related to a greater attention of the Bulgarian consumer towards the healthy action of the intake of polyunsaturated fatty acids in the prevention of cardiovascular diseases and hypertension and in the modulation of immunological and inflammatory responses (Kris-Etherton, Harris & Appel, 2002;Gottrand, 2008;Merdzhanova, Stancheva & Makedonski, 2012;Merdzhanova et al, 2017).…”
Section: Samples Collection: Frequency and Type Of Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high market availability and the increase in market demand of salmon, herring and mackerel, particularly rich in ω3 fatty acids, might be plausibly related to a greater attention of the Bulgarian consumer towards the healthy action of the intake of polyunsaturated fatty acids in the prevention of cardiovascular diseases and hypertension and in the modulation of immunological and inflammatory responses (Kris-Etherton, Harris & Appel, 2002;Gottrand, 2008;Merdzhanova, Stancheva & Makedonski, 2012;Merdzhanova et al, 2017).…”
Section: Samples Collection: Frequency and Type Of Productsmentioning
confidence: 99%
“…With the aim to further raise the awareness of consumers on seafood healthy characteristics, and promote the national products, studies have been conducted to highlight the content of polyunsaturated fatty acids (PUFA) of several Bulgarian fresh water and Black Sea species (carp, catfish, rainbow trout, sprat, turbot, garfish) (Merdzhanova, Ivanov, Dobreva & Makedonski, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids can be divided into saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), and PUFAs. Fish brain and eye are essential lipids sources in fish, rich in PUFAs, such as DHA and EPA [6]. Soyer et al [7] found that lipid oxidation of leg muscle in chicken was faster than breast muscle in the first 2 months during frozen storage, causing a great change in fatty acid composition.…”
Section: Introductionmentioning
confidence: 99%
“…It has good nutritional quality, highlighting the high protein content of high biological value, being a source of polyunsaturated fatty acids of the omega-3 (ω-3) (Eicosapentaenoic -EPA and Docosahexaenoic -DHA) and the omega 6 (ω-6) series (Arachidonic acid); oleic monounsaturated fatty acid and stearic saturated fatty acid (Lira et al, 2004). The benefits attributed to fish consumption are mainly related to the presence of polyunsaturated fatty acids in their composition, especially from the omega-3 series (Scherr et al, 2015;Merdzhanova et al, 2017).…”
Section: Introductionmentioning
confidence: 99%